Occurrence, Distribution, and Trophic Transfer of Pharmaceuticals and Personal Care Products in the Bohai Sea - Guo, Xiaotong; Lv, Min; Song, Lehui; Ding, Jing; Man, Mingsan; Fu, Longwen; Song, Zhihua; Li, Baoquan; Chen, Lingxin (Environmental science & technology, 2023)
The ubiquitous presence of pharmaceuticals and personal care products (PPCPs) in environments has aroused global concerns; however, minimal information is available regarding their multimedia distribution, bioaccumulation, and trophic transfer in marine environments. Herein, we analyzed 77 representative PPCPs in samples of surface and bottom seawater, surface sediments, and benthic biota from the Bohai Sea. PPCPs were pervasively detected in seawater, sediments, and benthic biota, with antioxidants being the most abundant PPCPs. PPCP concentrations positively correlated between the surface and bottom water with a decreasing trend from the coast to the central oceans. Higher PPCP concentrations in sediment were found in the Yellow River estuary, and the variations in the physicochemical properties of PPCPs and sediment produced a different distribution pattern of PPCPs in sediment from seawater. The log D ow, but not log K ow, showed a linear and positive relationship with bioaccumulation and trophic magnification factors and a parabolic relationship with biota-sediment accumulation factors. The trophodynamics of miconazole and acetophenone are reported for the first time. This study provides novel insights into the multimedia distribution and biomagnification potential of PPCPs and suggests that log D ow is a better indicator of their bioaccumulation and trophic magnification.